2022
DOI: 10.7759/cureus.29101
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Herpes Simplex Virus: A Histopathological View of the Placenta

Abstract: Congenital Herpes simplex virus (HSV) infection is considered a common pregnancy pathology that is not always easy to diagnose. This study aimed to present the spectrum of placental histopathological lesions in pregnancies complicated by HSV infection. MEDLINE and Google Scholar databases were searched using the keywords "HSV" and "placental histopathology" up to June 20, 2022. Study inclusion required presenting placental histopathological anomalies in pregnant women diagnosed with HSV infection antenatally, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…ToRCH pathogens represent the majority of placental infections associated with chronic inflammation [44], as they can enter the intra-amniotic space and overcome the defense mechanisms of the placenta that protect against vertical microbial transmission [42]. In the present study, the placental tissue examination revealed that CV was the main histopathological condition observed in the study population.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…ToRCH pathogens represent the majority of placental infections associated with chronic inflammation [44], as they can enter the intra-amniotic space and overcome the defense mechanisms of the placenta that protect against vertical microbial transmission [42]. In the present study, the placental tissue examination revealed that CV was the main histopathological condition observed in the study population.…”
Section: Discussionmentioning
confidence: 50%
“…It is noteworthy that few of the women were positive for NA only (Cat-VI) in the case of T.gondii and RV, while there was a high prevalence of CMV and HSV. Both the CMV and HSV cause latent infection [40,41], and it is quite possible that they evade the immune system and IgM and IgG may not be detected [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…In successful pregnancies, infant mortality rates are similarly associated with infection [92] . HSV infection has also been shown to induce significant pathologies in the placenta including chronic placental inflammation, chronic chorioamnionitis and villitis, and necrotic conditions [93] , which likely contribute to the associations between infection and pregnancy complications and/or failures.…”
Section: Hsv Effects On Reproduction and Across Generationsmentioning
confidence: 99%